Women Empowerment in Manju Kapur’s A Married Women - S., Uma Maheshwari (International Journal of Psychosocial Rehabilitation, 2020)
This paper, entitled Manju Kapur's "A Married Woman," manages the ladies strengthening through the voice of heroine Astha. It uncovered the situation of contemporary ladies in customary man-centric culture and bad habits for ladies' freedom from biased male strength. It criticizes the victimization lady and disassembles the conventional male-centric development to recoup their voice against concealment and sexual enslavement. The female protagonist of the novel, A Married Woman, Astha, who is the daughter of an education father and an education father and an orthodox mother, has an earnest desire for peaceful co-existence in the family. But she is discriminated against and subjugated at her in-law‘s house. There, she is supposed to have a willing body at night, a willing pair of hands and feet in the day, and an obedient mouth. Her marriage to Hemant, the son of a government official in Delhi, does not prove to be based on mutual cooperation and understanding. She is compelled to be an enduring wife and sacrifice others, like a holy cow in the status of a married woman. It leads to her physical exploitation and emotional starvation. Being deprived of her emotional fulfilment, she frantically searches for the fulfilment and turns to lesbianism. Manju Kapur in this novel, A Married Woman, through the protagonist Astha, advocates interreligious marriage and female-female bonding contrary to the patriarchal norms of traditional society.